Red Blood Cell 2,3-Diphosphoglycerate Decreases in Response to a 30 km Time Trial Under Hypoxia in Cyclists - Płoszczyca, Kamila; Czuba, Miłosz; Chalimoniuk, Małgorzata; Gajda, Robert; Baranowski, Marcin (Frontiers in Physiology, 2021)
Red blood cell 2,3-diphosphoglycerate (2,3-DPG) is one of the factors of rightward-shifted oxygen dissociation curves (ODC) and decrease of Hb-O2 affinity. The reduction of Hb-O2 affinity is beneficial to O2 unloading at the tissue level. In the current literature there are no studies about the changes in 2,3-DPG level following acute exercise in moderate hypoxia in athletes. For this reason, the aim of this study was to analyze the effect of prolonged intense exercise under normoxic and hypoxic conditions on 2,3-DPG level in cyclists. Fourteen male trained cyclists performed a simulation of a 30 km time trial (TT) in normoxia and normobaric hypoxia (FiO2=16.5%, ~2 000 m). During the TT the following variables were measured: power, blood oxygen saturation (SpO2) and heart rate (HR). Before and immediately after exercise the blood level of 2,3-DPG and acid-base equilibrium were determined. The results showed that the mean SpO2 during TT in hypoxia was 8% lower than in normoxia. The reduction of SpO2 in hypoxia resulted in a decrease of average power by 9.6% (p<0.001) and an increase in the 30 km TT completion time by 3.8% (p<0.01) compared to normoxia. The exercise in hypoxia caused a significant (p<0.001) decrease in 2,3-DPG level by 17.6%. After exercise in normoxia a downward trend of 2,3-DPG level was also observed, but this effect was not statistically significant. The analysis also revealed that changes of acid-base balance were significantly larger (p<0.05) after exercise in hypoxia than in normoxia. In conclusion, intense exercise in hypoxic conditions leads to a decrease in 2,3-DPG concentration, primarily due to exercise-induced acidosis.